Iberia; Spanish travels and reflections - Michener, James A. 1907-; Vavra, Robert (New York : Random House, 1968)
Summary: Since his first glimpse of it in 1932, Mr. Michener has returned to Spain many times, often for long visits, and his extensive travel and deep study there have given him abundantly the knowledge and insight on which to base this monumental book that he has for so long wanted to write
Contents: Badajoz -- Toledo -- Cordoba -- Las Marismas -- Sevilla -- Madrid -- Salamanca -- Pamplona -- Barcelona -- The Bulls -- Teruel -- Santiago De Compostela.
Keywords: Civilization; Spain -- Description and travel; Spain -- Civilization -- 20th century